The remediation of nano-/microplastics from water. (September 2021) - Sarcletti, Marco; Park, Hyoungwon; Wirth, Janis; Englisch, Silvan; Eigen, Andreas; Drobek, Dominik; Vivod, Dustin; Friedrich, Bernhard; Tietze, Rainer; Alexiou, Christoph; Zahn, Dirk; Apeleo Zubiri, Benjamin; et al.
Graphical abstract: Highlights: First concept for the sustainable remediation of nanoplastics from the environment. Use of superparamagnetic iron oxide nanoparticles for nanoplastics remediation. Remediation of different polymers relates to type of SPION. Applicability was confirmed in DI water as well as in contaminated and river water. Toxicological assessment confirmed harmlessness. Abstract: Nano-/microplastics (NP) is a human-made emerging contaminant with worldwide occurrence. The small size (below one micrometer), the different chemical nature and the persistence make NP to potential hazards with suspect probability of tissue penetration and inflammation or as accumulator for toxins. A strategy to stop the spill of novel NP is the remediation from waste water or rivers as prominent distributors. We have developed core–shell superparamagnetic iron oxide nanoparticles (SPIONs) that attract NP and glue them to larger agglomerates which then can be removed from water by applying an external magnetic field. The shell molecules provide two interaction motifs towards NP. The tuned surface potential of the functionalized SPIONs attract complementary charged NP efficiently and the n-alkyl chain is dedicated to preferential interaction towards organic NP rather than inorganic particles. Structural analytics and molecular dynamics simulation support the proposed concept. Systematic remediation experiments with different NP (chemical structures, sizes and mixtures), from different waters – including river water – and with different SPION core materials indicate a universal validity of the concept, with best remediation performance for mixed NP. We suggest a method for broadband remediation of various NP with simple materials and processes, which both have the potential to be up-scaled.